Bilateral Foramina Parietalia Permagna – A Calvarial Defect Caused by Haploinsufficiency of the Msh Homeobox 2 Gene: A Case Report and Current Literature Review - Kahl, Niklas; Lüsebrink, Natalia; Schubert-Bast, Susanne; Freiman, Thomas M.; Kieslich, Matthias (Neuropediatrics, 2024)
Foramina parietalia permagna (FPP) is a rare anatomical defect that affects the parietal bones of the human skull. FPP is characterized by symmetric perforations on either side of the skull, which are caused by insufficient ossification during embryogenesis. These openings are typically abnormally large and can range from a few millimeters to several centimeters in diameter. Enlarged foramina are often discovered incidentally during anatomical or radiological examinations and in most cases left untreated unless symptoms develop. Although this calvarial defect is usually asymptomatic, it may be accompanied by neurological or vascular conditions that can have clinical significance in certain cases. FPP is an inherited disorder and arises due to mutations in either Msh homeobox 2 (MSX2) or aristaless-like homeobox 4 (ALX4) genes. In almost all cases, one parent is affected. Clinical findings and diagnostic imaging typically contribute to determine the diagnosis.
Keywords: foramina parietalia permagna; MSX2; parietal bones; calvarial defect